Transnational Religious Spaces Religious Organizations and Interactions in Africa, East Asia, and Beyond - Clart, Philip / Jones (Dialectics of the Global, 2020)
This volume, bringing together work by scholars from Europe, East Asia, North America, and West Africa, investigates transnational religious spaces in a comparative manner by juxtaposing East Asian and African examples. It highlights flows of ideas, actors, and organizations out of, into, or within a given continental space. These flows are patterned mainly by colonialism or migration. The book also examines cases where the transnational space in question encompasses both East Asia and Africa, notably in the development of Japanese new religions in Africa. Most of the studies are located in the present a few go back to the late nineteenth century. The volume is rounded off by Thomas Tweed's systematic reflections on categories for the study of transnationalism his chapter Flows and Dams critically weighs the metaphorical language we use to think, speak, and write about transnational religious spaces.